Georgia in the World Merchandise Trade: Main Trends and Problems of Development - Korganashvili, Larisa (European Journal of Economics and Business Studies, 2018)
Foreign trade is the main factor in the country’s integration into the world economic system. It promotes the socio-economic development of states, especially developing countries. After the restoration of state independence, Georgia actively cooperates with different countries within the framework of bilateral and multilateral agreements. Its foreign trade activity is based on a high level of openness of the economy and liberal policy, features of the market economy and new vectors of development. Georgia has been a member of the World Trade Organization since 2000 and has one of the most liberal and competitive trade regimes across the world. Georgia’s foreign trade turnover has a cyclical growth pattern with a combination of periods of its fall. Over the entire post-Soviet period, the country has a negative trade balance and a high dependence on imports. Export characterizes a high degree of concentration of geographical structure and low level of diversification. The article analyzes the current state of Georgia’s foreign trade, shows the main indicators of the country’s foreign trade for the period of 1994-2014, and examines the main trends in its development and the importance of export diversification to improve the efficiency of foreign trade.